"My smartwatch told me to see a sleep doctor": a study of activity tracker use. Issue 2 (11th September 2019) - Pingo, Zablon; Narayan, Bhuva
Abstract : Purpose: The purpose of this paper is to investigate the use of wearable health and fitness trackers in everyday life, and users' motivations and their understanding and use of the data derived from devices, and understand the results using the lens of information behaviours. Design/methodology/approach: The study used a qualitative, constructionist approach, based on 21 interviews with users of a range of wearable activity trackers used for health and fitness. Findings: Findings show that the lifelogging devices have become companion tools that enable users to take information from their bodily indicators and make some decisions about their health and fitness, and also track the results when they act on it, thus giving them a sense of gratification and a sense of control over their own health. Practical implications: The findings have implications on how health professionals can talk to their lifelogging patients about how to deal with and understand the information provided by their activity-tracking devices. Some participants in the study already discuss these data regularly with their health professionals. Originality/value: As the self-tracking practices attract wide range research interests from human–computer interaction, information systems, digital sociology, health informatics and marketing among others. This study provides important everyday information-seeking perspective that contributes to the understanding of the practices of how people make sense of the data, how the data improves their wellbeing, i.e. physical health improvement or fitness, and implications to users health behaviour. Additionally the study adds to the lifelogging literature through a constructionist, qualitative approach rather than a technological deterministic approach.